Peripheral blood RNA gene expression profiling in patients with bacterial meningitis - Lill, Margit; Taba, Pille; Kõks, Sulev; Soomets, Ursel; Lutsar, Irja; Schalkwyk, Leonard C.; Fernandes, Cathy (Frontiers in Neuroscience, 2013)
The aim of present study was to find genetic pathways activated during infection with bacterial meningitis (BM) and potentially influencing the course of the infection using genome-wide RNA expression profiling combined with pathway analysis and functional annotation of the differential transcription. We analyzed 21 patients with BM hospitalized in 2008. The control group consisted of 18 healthy subjects. The RNA was extracted from whole blood, globin mRNA was depleted and gene expression profiling was performed using GeneChip Human Gene 1.0 ST Arrays which can assess the transcription of 28,869 genes. Gene expression profile data were analyzed using Bioconductor packages and Bayesian modeling. Functional annotation of the enriched gene sets was used to define the altered genetic networks. We also analyzed whether gene expression profiles depend on the clinical course and outcome. In order to verify the microarray results, the expression levels of ten functionally relevant genes with high statistical significance (CD177, IL1R2, IL18R1, IL18RAP, OLFM4, TLR5, CPA3, FCER1A, IL5RA, IL7R) were confirmed by quantitative real-time (qRT) PCR. There were 8569 genes displaying differential expression at a significance level of p <0.05. Following False Discovery Rate (FDR) correction, a total of 5500 genes remained significant at a p value of <0.01. Quantitative RT-PCR confirmed the differential expression in the 10 selected genes. Functional annotation and network analysis indicated that most of the genes were related to activation of humoral and cellular immune responses (enrichment score 43). Those changes were found in both adults and in children with BM compared to the healthy controls. There was a strong influence of the specific type of pathogen underlying BM. This study demonstrates that there is a very strong activation of immune response at the transcriptional level during BM and that the type of pathogen influences this transcriptional activation.